The Interplay of Nutrition, Physiology, and Performance in Sports: A Comprehensive Review - Irandoust , Khadijeh (Health Nexus, 2023)
This narrative review offers a thorough examination of the intricate relationship between nutrition, physiology, and sports performance. Drawing upon a wide array of scientific literature published between 2014 and 2023, this article synthesizes current research findings to elucidate how nutritional strategies and physiological factors coalesce to optimize athletic performance. The review employs a systematic approach, utilizing key databases such as PubMed, Google Scholar, Scopus, and Web of Science, and is inclusive of original research, comprehensive reviews, and expert commentaries in the fields of sports nutrition and exercise physiology. Central themes of the review include fundamental principles of sports nutrition, physiological determinants of athletic performance, specific nutritional strategies for enhancing performance, and the role of nutrition in injury prevention and recovery. Additionally, the review delves into practical applications and case studies, illustrating the real-world impact of nutrition-physiology interplay on sports performance. Through a critical analysis of the literature, this review identifies emerging trends, addresses current challenges in the field, and suggests future directions for research and practice. It aims to provide a holistic understanding for athletes, coaches, sports scientists, and nutritionists, emphasizing the necessity of integrating nutritional and physiological knowledge to advance sports performance. This comprehensive synthesis not only highlights the importance of individualized nutrition and training programs but also underscores the evolving nature of sports science in enhancing athletic achievement and health.